Retrospective study on disparities in time-to-treatment by health insurance system in Chilean breast cancer patients - ACEVEDO ROMO, JOHANNA PATRICIA; Teresa Ip; Lea Maureira; Cesar Sanchez; Claudia Osorio; Claudia Carvajal; ARAOS BRALIC, RAFAEL IGNACIO; Hernan Letelier; Francisco Acevedo; Tomas Merino (Medwave Estudios Limitada, 2025)
Introduction Breast cancer is the most common malignancy in the Americas, and the second leading cause of cancer death. Disparities in the time to treatment can significantly impact patient outcomes and typically affect lower socioeconomic individuals and/or ethnic minorities. Our study sought to evaluate disparities in time to treatment at three health institutions in Chile according to their type of health insurance (public or private). Methods Our study analyzed a database of breast cancer patients diagnosed between 2017 and 2018. Analyses included descriptive statistics and a linear regression model that incorporated clinical and demographic variables. Additionally, using a proportional risks model, we analyzed the association between clinical variables and mortality. Results Public health insurance (National Health Fund, FONASA) was associated with longer time-to-treatment and extended treatment times versus private health insurance (Social Security Institutions, ISAPRE; p < 0.0001). As expected, a more advanced stage at diagnosis was associated with lower survival. Our proportional risks model found that age was a predictor of breast cancer mortality in stage II patients. Also, total treatment time significantly increased the risk of breast cancer mortality in stage I patients. Conversely, total treatment time did not affect mortality on stages II or III. Conclusions We found significant disparities in the time to treatment of Chilean breast cancer patients using FONASA versus private ISAPRE. FONASA patients experience delays in the initiation of treatment and longer total treatment times compared to their private insurance counterparts. Finally, longer time-to-treatment was associated with more advanced stages and increased mortality.
Keywords: adult; age factors; aged; breast neoplasms; chile; databases; factual; female; healthcare disparities; humans; insurance; health; linear models; middle aged; neoplasm staging; retrospective studies; time factors; time-to-treatment; adult; age; aged; breast tumor; cancer staging; chile; comparative study; factual database; female; health care disparity; health insurance; human; middle aged; mortality; pathology; retrospective study; statistical model; therapy; time factor; time to treatment; breast cancer; healthcare disparities; mortality; public and private healthcare systems. time-to-treatment intervals